Team-based learning in an undergraduate pathology curriculum and its effects on student performance - Alwahab, Ahmed (J Taibah Univ Med Sci, 2018)
OBJECTIVES: Team-based learning (TBL) is a student-centered learning modality in which high and low achievers are organized in groups where students learn from each other at their own pace. The purpose of this study was to explore the correlations between TBL scores and final examination scores and student perceptions of a TBL system. METHODS: A cross-sectional survey was conducted on a sample obtained using quota sampling of a population of second-year students enrolled in the College of Medicine, University of Sharjah, Sharjah, United Arab Emirates. A self-administered questionnaire was employed to collect data on the students’ perceptions and opinions, TBL scores, and final examination scores. The data were processed and analyzed using SPSS Version 22. RESULTS: A sample of 101 students participated in the study. The Team Readiness Assurance Test scores were consistently higher than the mean Individual Readiness Assurance Test (IRAT) scores. The results found a statistically significant correlation between the IRAT and the final examination scores (r = 0.46, p < 0.001). About 57% of the sample agreed that TBL increased the understanding of course content, 45% reported that TBL was a useful learning activity, and 67% indicated that TBL enhanced interpersonal and communication skills. CONCLUSION: The findings imply that TBL is an effective tool to facilitate inter-professional and team-based learning outcomes. Collaborations among TBL group members help learners to develop communication and interpersonal skills and to gain knowledge.